Conocimiento y cuidado de enfermería del paciente politraumatizado de la Red de Salud Pacasmayo - Carranza Abanto, Cecilia Jacqueline (2019)
The present cross-sectional descriptive quantitative descriptive research work was carried out in 35 nurses working in the emergency service of the Pacasmayo Health Network, in order to determine the relationship between the level of knowledge and care practices of nursing to the polytraumatized patient in the emergency service. to whom two instruments were applied a survey on level of knowledge and the second a checklist on the practices of nursing care to the polytrauma patient, using the statistical test of chi-square to establish the relationship between the two variables concluding that The 100 % of the nurses of the Pacasmayo Health Network emergency service showed a bad level of knowledge. 77% poor nursing care practices and only 23% good practices. There is no significant relationship between the level of knowledge and nursing care practices of the polytrauma patient p = 0.142.